Interlayer chemical coupling long-acting noctilucent ceramic glaze as well as preparation method and application thereof
By using interlayer chemical coupling design and interfacial chemical reactions of multilayer structures, the problems of luminescent ceramic glaze attenuation in extreme environments and insufficient interlayer bonding are solved, achieving long-lasting, multi-color luminescence and high weather resistance, suitable for safety markings in petrochemical, power facilities, tunnels and offshore platforms.
Patent Information
- Application Number
- CN202511516660.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-23
- Publication Date
- 2025-11-21
- Estimated Expiration
- 2045-10-23
AI Technical Summary
Existing luminescent ceramic glazes exhibit rapid decay in luminescence performance under extreme industrial environments, have limited color luminescence, and insufficient interlayer bonding, failing to meet long-term usage requirements.
Employing an interlayer chemical coupling design, a two-step process of high-temperature primary firing and low-temperature secondary firing is used, combined with interfacial chemical reactions and stress release in a multilayer structure, and high thermal stability materials and nanocomposite systems are employed to enhance interlayer bonding strength and weather resistance.
It achieves long-lasting, multi-color luminescence and high weather resistance in extreme environments, improves interlayer bonding strength, can withstand multiple thermal shocks and corrosion, and has a lifespan far exceeding that of organic luminescent coatings.
Smart Images

Figure CN120987566A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of ceramic glaze production, in particular to a long-acting luminescent ceramic glaze with interlayer chemical coupling and a preparation method and application thereof. BACKGROUND
[0002] In extreme industrial environments such as petroleum chemical industry, power system, tunnel, offshore platform, clear and durable safety signs are essential for the safety of personnel and equipment. The widely used organic luminescent paint or signboard has problems such as poor weather resistance, easy aging and powdering, short service life, and cannot meet the long-term and maintenance-free use requirements.
[0003] It is recognized that the ideal way to solve the above problems is to incorporate luminescent powder into ceramic glaze to make luminescent ceramic. However, the existing luminescent ceramic glaze still has the following technical bottlenecks: first, the commonly used SrAl2O4:Eu,Dy luminescent powder will quickly decay in strong ultraviolet light and high temperature and humidity environment, and its luminescent color is single (mainly yellow-green), which limits the application scenarios. Second, the ultraviolet absorber added to protect the luminescent powder will continuously block the ultraviolet light, resulting in low “charging” efficiency of the luminescent powder in weak light environment such as cloudy days and evenings, forming a contradiction between “protection” and “excitation”. Third, due to the difference in thermal expansion coefficient and chemical properties between multi-layer functional glazes, the interlayer bonding strength is insufficient, and cracking or peeling occurs when the temperature changes dramatically.
[0004] Therefore, there is an urgent need in the art for a new type of luminescent ceramic glaze that can adapt to environmental changes, has ultra-long service life, multi-color luminescence and extreme weather resistance. SUMMARY
[0005] In view of the deficiencies in the prior art above, the purpose of the present application is to provide a long-acting luminescent ceramic glaze with interlayer chemical coupling, which has high interlayer bonding strength, excellent heat shock resistance and corrosion resistance through interface chemical coupling design.
[0006] Another purpose of the present application is to provide a preparation method of a long-acting luminescent ceramic glaze with interlayer chemical coupling, which adopts a two-step process of “high-temperature one-time firing + low-temperature secondary firing” to provide kinetic conditions for interface chemical reaction and stress release, ensuring the integrity and functionality of the multi-layer structure.
[0007] The third purpose of the present application is to provide an application of a long-acting luminescent ceramic glaze with interlayer chemical coupling, which is used in safety sign products of petroleum chemical facilities, power facilities, tunnels, offshore platforms or ships.
[0008] The present application is implemented by using the following technical solutions: The long-acting night light ceramic glaze with interlayer chemical coupling is a multi-layer composite structure arranged on a ceramic base, and sequentially comprises, from inside to outside: The bottom bonding glaze layer is sintered from first inorganic silicate raw materials; The core night light functional glaze layer is sintered from second inorganic silicate raw materials, long afterglow luminescent materials, and 4-6% niobium pentoxide in total mass of the core night light functional glaze layer; The photochromic protective surface glaze layer is sintered from third inorganic glass raw materials, nano tungsten trioxide, nano titanium dioxide, nano cerium oxide, and CaS:Eu 2+ , Tm 3+ .
[0009] The total mass ratio of the nano tungsten trioxide, nano titanium dioxide, nano cerium oxide, and CaS:Eu 2+ , Tm 3+ in the surface glaze layer is 14.5-26.5%.
[0010] The long afterglow luminescent material is a core-shell composite structure, the core of which is an alkali earth metal silicate doped with Eu 2+ and Ho 3+ , and the shell is mesoporous silica.
[0011] In the bottom bonding glaze layer, the first inorganic silicate raw materials include, by weight percentage, feldspar 38-42%; quartz 23-27%; calcite 10-14%; zinc oxide 6-9%; kaolin 8-11%; and zircon 4-6%.
[0012] The second inorganic silicate raw materials are calcium-zinc borosilicate glass frit and active silicon dioxide; and the raw materials of the core night light functional glaze layer include, by weight percentage, calcium-zinc borosilicate glass frit 68-72%; long afterglow luminescent materials 15-23%; active silicon dioxide 4-6%; and niobium pentoxide 4-6%.
[0013] The raw materials of the photochromic protective surface glaze layer include, by weight percentage, phosphate glass powder 74-82%; nano tungsten trioxide 2-4%; nano titanium dioxide 8-11%; nano cerium oxide 0.5-1.5%; and CaS:Eu 2+ , Tm 3+ : 4-10%.
[0014] The preparation method of the long-acting night light ceramic glaze with interlayer chemical coupling comprises the following steps: (1) applying the bottom bonding glaze layer and the core night light functional glaze layer on the ceramic base in sequence, and performing high-temperature one-time sintering to obtain a night light glaze base; (2) applying a photochromic protective glaze layer on the noctilucent glaze substrate, and performing low-temperature secondary firing to obtain the long-acting noctilucent ceramic glaze; The peak temperature of the high-temperature primary firing is 1220-1240℃. The peak temperature of the low-temperature secondary firing is 780-820℃.
[0015] The high-temperature primary firing process comprises: heating from room temperature to 600℃ at a rate of 2-4℃ / min, heating to 900℃ at a rate of 1-2℃ / min, and finally heating to the peak temperature at a rate of 4-6℃ / min and maintaining for 15-25min; after firing, cooling to 950℃ at a rate of 4-6℃ / min, and then cooling to 750℃ at a rate of 1-2℃ / min.
[0016] The low-temperature secondary firing process comprises: heating from room temperature to 500℃ at a rate of 4-6℃ / min, heating to 700℃ at a rate of 1-3℃ / min, and finally heating to the peak temperature at a rate of 7-9℃ / min and maintaining for 5-10min; after firing, cooling to 550℃ at a rate of 1-3℃ / min.
[0017] The long-acting noctilucent ceramic glaze with interlayer chemical coupling is applied to safety sign products of petroleum and chemical facilities, power facilities, tunnels, offshore platforms or ships.
[0018] Specifically, the preparation method of the long-acting noctilucent ceramic glaze with interlayer chemical coupling comprises: Raw material pretreatment: Quartz: calcined at 980-1020℃ for 1.5-2.5h, water quenched and ball milled to D50<10μm.
[0019] Zinc oxide: calcined at 750-850℃ for 1-1.5h.
[0020] Niobium pentoxide: calcined at 800-900℃ for 1.5-2.5h, and then ball milled to D50<3μm.
[0021] Nanopowder (WO3, TiO2): mixed with 3-5% of polyacrylammonium dispersant and 25-30% of ethyl cellulose carrier by weight, and ultrasonic treated for 20-40min.
[0022] Surface coating pretreatment of CaS:Eu 2+ , Tm 3+ Ball milling: ball milling the CaS:Eu 2+ , Tm 3+ powder to D50<2μm.
[0023] Coating: After ball milling, the CaS powder was dispersed in a mixed solution of ethanol and water, 1-2% of TEOS (tetraethyl orthosilicate) and a catalytic amount of ammonia water (0.5-1.5% of the mass of the CaS powder, ammonia water concentration: 25%) were added, and the mixture was stirred and reacted at 40-60°C for 4-6 hours.
[0024] Post-processing: After the reaction was completed, centrifugation, washing, and drying at 80°C were performed, and finally, the CaS@SiO2 composite powder with a dense nanometer SiO2 protective layer was formed by heat treatment at 400°C for 1 hour in an inert atmosphere (N2).
[0025] Preparation of core-shell composite long afterglow luminescent material, comprising the following steps: a. Core synthesis (Ba 1.95 Sr 0.05 SiO4:Eu 0.01 ,Ho 0.02 ) Batching and ball milling: The ingredients were weighed according to the stoichiometric ratio, 1-3wt% H3BO3 was added as a fluxing agent, and high-energy ball milling was performed for 10-14h in anhydrous ethanol medium.
[0026] Pre-burning: After drying, pre-burning was performed at 1130-1170°C for 2-4h in a weak reducing atmosphere (95% N2+5% H2).
[0027] Final burning: After 5-7h of re-milling, sintering was performed at 1230-1270°C for 3-5h in the same atmosphere.
[0028] Annealing: Precise annealing was performed at a rate of -4~-6°C / min from the peak temperature to 800°C, and at a rate of -1~-2°C / min from 800°C to 300°C, followed by furnace cooling.
[0029] b. Core-shell structure construction (Core@mSiO2) Coating: The core powder was dispersed in a solution containing ethanol, water, and 0.1-0.2wt% CTAB.
[0030] Reaction: TEOS and ammonia water were slowly added dropwise, and the mixture was stirred and reacted at 35-45°C for 5-7h.
[0031] Post-processing: After centrifugation, washing, and drying, calcination was performed in air at 520-580°C for 3-5h.
[0032] Finished product: The powder was collected and vacuum dried at 60°C to obtain the final product.
[0033] Glaze preparation and sintering process Glaze preparation: Enamel slip of bottom bonding layer and core luminescent functional layer: Respectively according to the formula, add deionized water (solid content 58-65%) and 0.2-0.5wt% of sodium tripolyphosphate dispersant, ball mill for 16-24h, until the fineness D90<25μm. The mill-out specific gravity is controlled at 1.40-1.50g / cm 3 .
[0034] Photochromic protective surface enamel layer paste: The powder and the organic carrier are mixed in a weight ratio of 1:1.1-1.3, and are ground by a three-roll grinder for 4-6 times until the fineness is <20μm. The organic carrier is a mixture composed of 8% of ethyl cellulose, 85% of terpineol and 7% of dibutyl phthalate.
[0035] Glazing and sintering process Substrate preparation: Clean and dry the ceramic plate.
[0036] Glazing 1 (bottom bonding enamel layer): Spray glazing, wet film thickness 0.2-0.4mm, room temperature drying for 1-3h.
[0037] Glazing 2 (core luminescent functional enamel layer): Spray glazing, wet film thickness 0.3-0.5mm, room temperature drying for 3-5h.
[0038] High-temperature one-time sintering (bottom layer + core layer): Sintering curve: Room temperature→600℃(2-4℃ / min); 600℃→900℃(1-2℃ / min); 900℃→1220-1240℃(4-6℃ / min); Peak temperature holding for 15-25min.
[0039] Annealing curve: Peak temperature→950℃(4~6℃ / min); 950℃→750℃(1~2℃ / min); 750℃→300℃(2~4℃ / min); 300℃→room temperature (cooling with the furnace).
[0040] Glazing 3 (photochromic protective surface enamel layer): Screen printing, control the dry film thickness at 20-40μm, drying at 70-90℃ for 20-40min.
[0041] Low-temperature two-time sintering (surface enamel layer): Sintering curve: Room temperature→500℃(4-6℃ / min, degassing); 500℃→700℃(1-3℃ / min, two-time coupling platform); 700℃→780-820℃(7-9℃ / min); Peak temperature holding 5-10 min.
[0042] Annealing curve: Peak temperature→550℃(1~3℃ / min, stress release zone); 550℃→300℃(3~5℃ / min); 300℃→room temperature (furnace cooling).
[0043] The present application discards the single luminescent material or structure which is unstable at high temperature, and creatively composites a blue-green luminescent alkaline earth metal silicate core with an orange-red long afterglow material with high thermal stability. By precisely controlling the proportion of the two, using the principle of additive color mixing of light color, the emission spectrum of them is visually superimposed, so that the continuous and tunable luminescent color from cold white to warm white is realized. The introduction of niobium pentoxide (Nb2O5) in the core glaze layer not only acts as a network former or modifier inside the glaze layer, but more importantly, it can react in situ with zinc ions (Zn 2+ ) and the like diffused from the bottom glaze to form enhanced crystal phases such as niobium-zinc compounds at the interface. These crystal phases, like "chemical rivets", penetrate through the multi-layer interface, realizing the leap from physical combination to chemical bonding, greatly improving the interlayer bonding force and thermal shock resistance. The WO3 / TiO2 / CeO2 nanocomposite system in the surface glaze layer constitutes a response system. Among them, CeO2, with its unique energy band structure, improves the net charging efficiency by energy transfer or inhibits the negative photocatalytic effect of TiO2 under weak light. The preparation method of the glaze adopts the two-step process of "high-temperature one-time firing + low-temperature secondary firing", and by precisely controlling the heating / cooling rate, especially setting the slow heating platforms of 600-900℃ and 500-700℃ and the slow cooling intervals of 950-750℃ and 800-550℃, the kinetic conditions are provided for the interface chemical reaction and stress release, ensuring the integrity and functionality of the multi-layer structure.
[0044] Compared with the prior art, the present application has the following beneficial effects: (1) By compositing the orange-red long afterglow material with extremely high thermal stability with the blue-green core, the present application fundamentally solves the problem that the traditional ZnS material cannot withstand high-temperature firing. The composite luminescent system can still maintain excellent luminescent performance after being fired at a high temperature of 1220-1240℃.
[0045] (2) By introducing key components such as Nb2O5 and zircon, a "chemical rivet" crystal phase is generated in situ at the interlayer interface, transforming the traditional physical adhesion into a strong chemical bond. This increases the interlayer bonding strength of the glaze to over 20 MPa, and its thermal shock resistance exceeds 50 cycles. It can withstand long-term thermal shock and corrosion in extreme environments such as petroleum, chemical, and marine environments, and its lifespan far exceeds that of organic luminous coatings.
[0046] (3) The two-step process of "high-temperature primary firing + low-temperature secondary firing" is adopted, and the precise control of the heating / cooling curves provides sufficient kinetic conditions for interface reaction, stress release and preservation of functional structure. The process has a wide parameter window, moderate equipment requirements, and is easy to achieve stable and controllable large-scale production. Attached Figure Description
[0047] Figure 1 Ba obtained in Embodiment 3 of the present invention 1.95 Sr 0.05 SiO4:Eu 0.01 Ho 0.02 The emission spectrum of the phosphorescent powder was measured at 365nm as the monitoring wavelength.
[0048] Figure 2 Ba obtained in Examples 1-3 of the present invention 1.95 Sr 0.05 SiO4:Eu 0.01 Ho 0.02 The excitation spectrum of the phosphorescent powder was measured at 500 nm as the monitoring wavelength. Detailed Implementation
[0049] To make the objectives and technical solutions of this invention clearer, the invention will be further described in detail below.
[0050] Feldspar: Xiangtan Zhonghan Feldspar Mining Co., Ltd., potassium feldspar, K2O content ≥10%, particle size D50≤15μm; Quartz: Jiangsu Pacific Quartz Co., Ltd., SiO2 content ≥99.9%, ball-milled to D50≤8μm after calcination at 1000℃; Calcite: Guilin Jinshan New Materials Co., Ltd., heavy calcium carbonate, CaCO3 content ≥98.5%, particle size D50≤5μm; Zinc oxide: Liuzhou Zinc Products Co., Ltd., indirect zinc oxide, ZnO content ≥99.5%, calcined at 800℃; Kaolin: China Kaolin Co., Ltd. (Suzhou), calcined kaolin, Al2O3 content ≥40%, particle size D50≤2μm; Zircon: Guangdong Oriental Zircon Industry Technology Co., Ltd., ultrafine zircon powder, ZrSiO4 content ≥99%, particle size D50~2μm; Calcium-zinc borosilicate glass frit: SiO2: 52%-58%; B2O3: 6%-10%; CaO: 8%-15%; ZnO: 5%-9%; Al2O3: 2%-5%; other impurities ≤0.5%, softening point 850±10℃, coefficient of thermal expansion (6.0±0.2)×10 -6 / K; Activated silica: Evonik Industries, AEROSIL ® 200, specific surface area 200±25m² 2 / g; Niobium pentoxide: Luoyang Luanchuan Molybdenum Group Co., Ltd., Nb2O5 content ≥99.9%, calcined at 850℃ and then ball-milled to D50≤3μm; Phosphate glass powder: P2O5: 45%-55%; ZnO: 10%-18%; Na2O: 3%-8%; CaO: 5%-12%; Al2O3: 1%-4%, softening point 650±10℃; Nano WO3: Shanghai Aladdin Biochemical Technology Co., Ltd., particle size <50nm, purity 99.9%; Nano TiO2: Degussa GmbH, Germany, P25, anatase type, particle size approximately 21 nm; Nano CeO2: Shandong Guoci Functional Materials Co., Ltd., CeO2 content ≥99.9%, particle size 30-50nm; Long-afterglow phosphorescent powder SrMgAl4O8:Eu 2+ Dy 3+ Dalian Luming Luminescent Light Technology Co., Ltd. Borosilicate: Schott Group, Germany; SiO2: 81-83%, B2O3: 13-15%, Na2O / K2O: 4-5%; Coefficient of thermal expansion: 3.3 × 10⁻⁶ -6 / K (20-300℃); V2O5: Sinopharm Chemical Reagent Co., Ltd. CaS:Eu 2+ Tm 3+ : GRINM Rare Earth New Materials Co., Ltd.
[0051] Raw material pretreatment Quartz: calcined at 1000℃ for 2 hours, water quenched, and then ball-milled until D50 < 10 μm.
[0052] Zinc oxide: calcined at 800℃ for 1.5h.
[0053] Niobium pentoxide: calcined at 850℃ for 2 hours, then ball-milled until D50 < 3 μm.
[0054] Nanoparticles (WO3, TiO2): Mixed with 4% by weight of ammonium polyacrylate and 30% by weight of carrier (8% ethyl cellulose, 85% terpineol and 7% dibutyl phthalate), and ultrasonically treated for 30 min.
[0055] CaS:Eu 2+ ,Tm 3+ Surface coating pretreatment: Ball milling: CaS:Eu 2+ Tm 3+ Powder (source: e.g., Beijing Zhongke Rare Earth New Materials Co., Ltd.) is ball-milled to D50 < 2 μm.
[0056] Coating: Disperse the ball-milled CaS powder in a mixed solution of ethanol and water, add 2% tetraethyl orthosilicate (TEOS) by mass of CaS and ammonia water (added at 1% by mass of CaS powder, ammonia water concentration: 25%), and stir the reaction at 50°C for 5 hours.
[0057] Post-processing: After the reaction is complete, the powder is centrifuged, washed, and dried at 80°C. Finally, it is heat-treated at 400°C for 1 hour in an inert atmosphere (N2) to form CaS@SiO2 composite powder with a dense nano-SiO2 protective layer.
[0058] The firing atmosphere for the examples and comparative examples was a weak reducing atmosphere (N2 protection).
[0059] Example 1 The preparation of core-shell composite structure long afterglow luminescent materials includes the following steps: a. Core Synthesis (Ba 1.95 Sr 0.05 SiO4:Eu 0.01 Ho 0.02 ) Ingredients and ball milling: Weigh according to stoichiometric ratio, add 1wt% H3BO3 as flux, and ball mill for 10 hours with anhydrous ethanol as medium.
[0060] Pre-calcination: After drying, pre-calcinate at 1130℃ for 2 hours under a weak reducing atmosphere (95% N2 + 5% H2).
[0061] Final firing: After ball milling for 5 hours again, sinter at 1230℃ for 3 hours under the same atmosphere.
[0062] Annealing: Perform precise annealing, from peak temperature to 800℃ at a rate of 4℃ / min; from 800℃ to 300℃ at a rate of 1℃ / min; followed by furnace cooling. Ba 1.95 Sr0.05 SiO4:Eu 0.01 Ho 0.02 The excitation spectrum of the phosphorescent powder, measured at a monitoring wavelength of 500 nm, is shown below. Figure 2 .
[0063] b. Core-shell structure construction (Core@mSiO2) Coating: The core luminescent powder is dispersed in a solution containing ethanol, water and 0.1 wt% CTAB.
[0064] Reaction: TEOS and ammonia were slowly added dropwise, and the mixture was stirred at 35°C for 5 hours.
[0065] Post-treatment: After centrifugation, washing, and drying, calcination was carried out in air at 520℃ for 3 hours.
[0066] Finished product: Collect the powder and dry it under vacuum at 60℃.
[0067] The amount and ratio of each raw material are shown in Table 1.
[0068] A method for preparing long-lasting luminescent ceramic glaze with interlayer chemical coupling includes the following steps: (1) Apply a bottom layer of bonding glaze and a core luminescent functional glaze layer sequentially to a ceramic substrate, and fire it once at high temperature to obtain a luminescent glaze substrate; The base glaze layer and the core luminescent functional glaze layer slurry were weighed according to the formula, and deionized water (58% solid content) and 0.2wt% dispersant were added. The mixture was ball-milled for 16 hours until a fineness D90 < 25μm was achieved. The specific gravity exiting the mill was controlled at 1.40 g / cm³. 3 .
[0069] Photochromic protective glaze paste: The powder and organic carrier are mixed at a weight ratio of 1:1.1 and milled four times with a three-roll mill until the fineness is <20μm. The organic carrier is a mixture of 8% ethyl cellulose, 85% terpineol and 7% dibutyl phthalate.
[0070] Glazing and sintering process Substrate preparation: Clean and dry the ceramic plate.
[0071] Glazing 1 (bottom layer combined with glaze): Spray glaze, wet film thickness 0.2mm, dry at room temperature for 1 hour.
[0072] Glazing 2 (core luminous functional glaze layer): Spray glaze, wet film thickness 0.3mm, dry at room temperature for 3 hours.
[0073] The high-temperature single-firing process includes: heating from room temperature to 600℃ at 2℃ / min, then heating to 900℃ at 1℃ / min, and finally heating to the peak temperature at 4℃ / min and holding for 15min; after firing, cooling to 950℃ at 4℃ / min and then cooling to 750℃ at 1℃ / min.
[0074] (2) A photochromic protective glaze layer is applied to the luminous glaze substrate, and then fired at low temperature for a second time to obtain the long-lasting luminous ceramic glaze. Glazing 3 (photochromic protective glaze layer): screen printing, control the dry film thickness to 20μm, dry at 70℃ for 20min.
[0075] The low-temperature secondary firing process includes: heating from room temperature to 500℃ at 4℃ / min, then heating to 700℃ at 1℃ / min, and finally heating to the peak temperature at 7℃ / min and holding for 5 minutes; after firing, cooling to 550℃ at 1℃ / min.
[0076] The peak temperature of the high-temperature single firing is 1220℃; the peak temperature of the low-temperature double firing is 780℃.
[0077] Example 2 The preparation of core-shell composite structure long afterglow luminescent materials includes the following steps: a. Core Synthesis (Ba 1.95 Sr 0.05 SiO4:Eu 0.01 Ho 0.02 ) Ingredients and ball milling: Weigh according to stoichiometric ratio, add 3wt% H3BO3 as flux, and ball mill for 14 hours with anhydrous ethanol as medium.
[0078] Pre-calcination: After drying, pre-calcinate at 1170℃ for 4 hours in a weak reducing atmosphere (95% N2 + 5% H2).
[0079] Final firing: After ball milling for 7 hours again, sinter at 1270℃ for 5 hours under the same atmosphere.
[0080] Annealing: Perform precise annealing, from peak temperature to 800℃ at a rate of 6℃ / min; from 800℃ to 300℃ at a rate of 2℃ / min; followed by furnace cooling. Ba 1.95 Sr 0.05 SiO4:Eu 0.01 Ho 0.02 The excitation spectrum of the phosphorescent powder, measured at a monitoring wavelength of 500 nm, is shown below. Figure 2 .
[0081] b. Core-shell structure construction (Core@mSiO2) Coating: The core luminescent powder is dispersed in a solution containing ethanol, water and 0.2 wt% CTAB.
[0082] Reaction: TEOS and ammonia were slowly added dropwise, and the mixture was stirred at 45°C for 7 hours.
[0083] Post-treatment: After centrifugation, washing, and drying, calcination was carried out in air at 580℃ for 5 hours.
[0084] Finished product: Collect the powder and dry it under vacuum at 60℃.
[0085] The amount and ratio of each raw material are shown in Table 1.
[0086] A method for preparing long-lasting luminescent ceramic glaze with interlayer chemical coupling includes the following steps: (1) Apply a bottom layer of bonding glaze and a core luminescent functional glaze layer sequentially to a ceramic substrate, and fire it once at high temperature to obtain a luminescent glaze substrate; The base glaze layer and the core luminescent functional glaze layer slurry were weighed according to the formula, and deionized water (65% solid content) and 0.5wt% dispersant were added. The mixture was ball-milled for 24 hours until a fineness D90 < 25μm was achieved. The specific gravity exiting the mill was controlled at 1.50 g / cm³. 3 .
[0087] Photochromic protective glaze paste: The powder and organic carrier are mixed at a weight ratio of 1:1.3 and then ground 6 times with a three-roll mill until the fineness is <20μm. The organic carrier is a mixture of 8% ethyl cellulose, 85% terpineol and 7% dibutyl phthalate.
[0088] Glazing and sintering process Substrate preparation: Clean and dry the ceramic plate.
[0089] Glazing 1 (bottom layer combined with glaze): Spray glaze, wet film thickness 0.4mm, dry at room temperature for 3 hours.
[0090] Glazing 2 (core luminous functional glaze layer): Spray glaze, wet film thickness 0.5mm, dry at room temperature for 5 hours.
[0091] The high-temperature single-firing process includes: heating from room temperature to 600℃ at 4℃ / min, then heating to 900℃ at 2℃ / min, and finally heating to the peak temperature at 6℃ / min and holding for 25 minutes; after firing, cooling to 950℃ at 6℃ / min and then cooling to 750℃ at 2℃ / min.
[0092] (2) A photochromic protective glaze layer is applied to the luminous glaze substrate, and then fired at low temperature for a second time to obtain the long-lasting luminous ceramic glaze. Glazing 3 (photochromic protective glaze layer): screen printing, control the dry film thickness to 40μm, and dry at 90℃ for 40min.
[0093] The low-temperature secondary firing process includes: heating from room temperature to 500°C at 6°C / min, then heating to 700°C at 3°C / min, and finally heating to the peak temperature at 9°C / min and holding for 10 min; after firing, cooling to 550°C at 3°C / min.
[0094] The peak temperature of the high-temperature single firing is 1240℃; the peak temperature of the low-temperature double firing is 820℃.
[0095] Example 3 The preparation of core-shell composite structure long afterglow luminescent materials includes the following steps: a. Core Synthesis (Ba 1.95 Sr 0.05 SiO4:Eu 0.01 Ho 0.02 ) Ingredients and ball milling: Weigh according to stoichiometric ratio, add 2wt% H3BO3 as flux, and ball mill for 12 hours with anhydrous ethanol as medium.
[0096] Pre-calcination: After drying, pre-calcinate at 1150℃ for 3 hours under a weak reducing atmosphere (95% N2 + 5% H2).
[0097] Final firing: After ball milling for 6 hours again, sinter at 1250℃ for 4 hours under the same atmosphere.
[0098] Annealing: Perform precise annealing, from peak temperature to 800℃ at a rate of 5℃ / min; from 800℃ to 300℃ at a rate of 2℃ / min; followed by furnace cooling. Ba 1.95 Sr 0.05 SiO4:Eu 0.01 Ho 0.02 The excitation spectrum of the phosphorescent powder, measured at a monitoring wavelength of 500 nm, is shown below. Figure 2 The emission spectrum measured at 365nm as the monitoring wavelength is shown below. Figure 1 .
[0099] b. Core-shell structure construction (Core@mSiO2) Coating: The core luminescent powder is dispersed in a solution containing ethanol, water and 0.2 wt% CTAB.
[0100] Reaction: TEOS and ammonia were slowly added dropwise, and the mixture was stirred at 40°C for 6 hours.
[0101] Post-treatment: After centrifugation, washing, and drying, calcination was carried out in air at 550°C for 4 hours.
[0102] Finished product: Collect the powder and dry it under vacuum at 60℃.
[0103] The amount and ratio of each raw material are shown in Table 1.
[0104] A method for preparing long-lasting luminescent ceramic glaze with interlayer chemical coupling includes the following steps: (1) Apply a bottom layer of bonding glaze and a core luminescent functional glaze layer sequentially to a ceramic substrate, and fire it once at high temperature to obtain a luminescent glaze substrate; The base glaze layer and the core luminescent functional glaze layer slurry were weighed according to the formula, and deionized water (60% solid content) and 0.3wt% dispersant were added. The mixture was ball-milled for 20 hours until a fineness D90 < 25μm was achieved. The specific gravity exiting the mill was controlled at 1.45 g / cm³. 3 .
[0105] Photochromic protective glaze paste: The powder and organic carrier are mixed at a weight ratio of 1:1.2 and milled five times with a three-roll mill until the fineness is <20μm. The organic carrier is a mixture of 8% ethyl cellulose, 85% terpineol and 7% dibutyl phthalate.
[0106] Glazing and sintering process Substrate preparation: Clean and dry the ceramic plate.
[0107] Glazing 1 (bottom layer combined with glaze): Spray glaze, wet film thickness 0.3mm, dry at room temperature for 2 hours.
[0108] Glazing 2 (core luminous functional glaze layer): Spray glaze, wet film thickness 0.4mm, dry at room temperature for 4 hours.
[0109] The high-temperature single-firing process includes: heating from room temperature to 600℃ at 3℃ / min, then heating to 900℃ at 2℃ / min, and finally heating to the peak temperature at 5℃ / min and holding for 20min; after firing, cooling to 950℃ at 5℃ / min and then cooling to 750℃ at 2℃ / min.
[0110] (2) A photochromic protective glaze layer is applied to the luminous glaze substrate, and then fired at low temperature for a second time to obtain the long-lasting luminous ceramic glaze. Glazing 3 (photochromic protective glaze layer): screen printing, control the dry film thickness to 30μm, dry at 80℃ for 30min.
[0111] The low-temperature secondary firing process includes: heating from room temperature to 500℃ at 5℃ / min, then heating to 700℃ at 2℃ / min, and finally heating to the peak temperature at 8℃ / min and holding for 8 minutes; after firing, cooling to 550℃ at 2℃ / min.
[0112] The peak temperature of the high-temperature single firing is 1230℃; the peak temperature of the low-temperature double firing is 800℃.
[0113] Example 4 The preparation of core-shell composite structure long afterglow luminescent materials includes the following steps: a. Core Synthesis (Ba 1.95 Sr 0.05 SiO4:Eu 0.01 Ho 0.02 ) Ingredients and ball milling: Weigh according to stoichiometric ratio, add 1wt% H3BO3 as flux, and ball mill for 14 hours with anhydrous ethanol as medium.
[0114] Pre-calcination: After drying, pre-calcinate at 1170℃ for 2 hours under a weak reducing atmosphere (95% N2 + 5% H2).
[0115] Final firing: After ball milling for 7 hours again, sinter at 1270℃ for 3 hours under the same atmosphere.
[0116] Annealing: Perform precise annealing from peak temperature to 800°C at a rate of 6°C / min; from 800°C to 300°C at a rate of 2°C / min; followed by furnace cooling.
[0117] b. Core-shell structure construction (Core@mSiO2) Coating: The core powder is dispersed in a solution containing ethanol, water and 0.2 wt% CTAB.
[0118] Reaction: TEOS and ammonia were slowly added dropwise, and the mixture was stirred at 45°C for 5 hours.
[0119] Post-treatment: After centrifugation, washing, and drying, calcination was carried out in air at 580℃ for 3 hours.
[0120] Finished product: Collect the powder and dry it under vacuum at 60℃.
[0121] The amount and ratio of each raw material are shown in Table 1.
[0122] A method for preparing long-lasting luminescent ceramic glaze with interlayer chemical coupling includes the following steps: (1) Apply a bottom layer of bonding glaze and a core luminescent functional glaze layer sequentially to a ceramic substrate, and fire it once at high temperature to obtain a luminescent glaze substrate; The base glaze layer and the core luminescent functional glaze layer slurry were weighed according to the formula, and deionized water (65% solid content) and 0.5wt% dispersant were added. The mixture was ball-milled for 24 hours until a fineness D90 < 25μm was achieved. The specific gravity exiting the mill was controlled at 1.50 g / cm³. 3 .
[0123] Photochromic protective glaze paste: The powder and organic carrier are mixed at a weight ratio of 1:1.3 and then ground four times with a three-roll mill until the fineness is <20μm. The organic carrier is a mixture of 8% ethyl cellulose, 85% terpineol, and 7% dibutyl phthalate.
[0124] Glazing and sintering process Substrate preparation: Clean and dry the ceramic plate.
[0125] Glazing 1 (bottom layer combined with glaze): Spray glaze, wet film thickness 0.4mm, dry at room temperature for 1 hour.
[0126] Glazing 2 (core luminous functional glaze layer): Spray glaze, wet film thickness 0.5mm, dry at room temperature for 3 hours.
[0127] The high-temperature single-firing process includes: heating from room temperature to 600℃ at 4℃ / min, then heating to 900℃ at 2℃ / min, and finally heating to the peak temperature at 6℃ / min and holding for 25 minutes; after firing, cooling to 950℃ at 6℃ / min and then cooling to 750℃ at 2℃ / min.
[0128] (2) A photochromic protective glaze layer is applied to the luminous glaze substrate, and then fired at low temperature for a second time to obtain the long-lasting luminous ceramic glaze. Glazing 3 (photochromic protective glaze layer): screen printing, control the dry film thickness to 40μm, dry at 90℃ for 20min.
[0129] The low-temperature secondary firing process includes: heating from room temperature to 500°C at 6°C / min, then heating to 700°C at 3°C / min, and finally heating to the peak temperature at 9°C / min and holding for 10 min; after firing, cooling to 550°C at 3°C / min.
[0130] The peak temperature of the high-temperature single firing is 1240℃; the peak temperature of the low-temperature double firing is 820℃.
[0131] Example 5 The preparation of core-shell composite structure long afterglow luminescent materials includes the following steps: a. Core Synthesis (Ba 1.95 Sr 0.05 SiO4:Eu 0.01 Ho 0.02 ) Ingredients and ball milling: Weigh according to stoichiometric ratio, add 1wt% H3BO3 as flux, and ball mill for 10 hours with anhydrous ethanol as medium.
[0132] Pre-calcination: After drying, pre-calcinate at 1130℃ for 4 hours in a weak reducing atmosphere (95% N2 + 5% H2).
[0133] Final firing: After ball milling for 5 hours again, sinter at 1230℃ for 5 hours under the same atmosphere.
[0134] Annealing: Perform precise annealing from peak temperature to 800°C at a rate of 6°C / min; from 800°C to 300°C at a rate of 2°C / min; followed by furnace cooling.
[0135] b. Core-shell structure construction (Core@mSiO2) Coating: The core powder is dispersed in a solution containing ethanol, water and 0.1 wt% CTAB.
[0136] Reaction: TEOS and ammonia water were slowly added dropwise, and the mixture was stirred at 35°C for 5-7 hours.
[0137] Post-treatment: After centrifugation, washing, and drying, calcination was carried out in air at 520℃ for 5 hours.
[0138] Finished product: Collect the powder and dry it under vacuum at 60℃.
[0139] The amount and ratio of each raw material are shown in Table 1.
[0140] A method for preparing long-lasting luminescent ceramic glaze with interlayer chemical coupling includes the following steps: (1) Apply a bottom layer of bonding glaze and a core luminescent functional glaze layer sequentially to a ceramic substrate, and fire it once at high temperature to obtain a luminescent glaze substrate; The base glaze layer and the core luminescent functional glaze layer slurry were weighed according to the formula, and deionized water (58% solid content) and 0.2wt% dispersant were added. The mixture was ball-milled for 16 hours until a fineness D90 < 25μm was achieved. The specific gravity exiting the mill was controlled at 1.40 g / cm³. 3 .
[0141] Photochromic protective glaze paste: The powder and organic carrier are mixed at a weight ratio of 1:1.1-1.3 and ground four times with a three-roll mill until the fineness is <20μm. The organic carrier is a mixture of 8% ethyl cellulose, 85% terpineol and 7% dibutyl phthalate.
[0142] Glazing and sintering process Substrate preparation: Clean and dry the ceramic plate.
[0143] Glazing 1 (bottom layer combined with glaze): Spray glaze, wet film thickness 0.2mm, dry at room temperature for 1 hour.
[0144] Glazing 2 (core luminous functional glaze layer): Spray glaze, wet film thickness 0.3mm, dry at room temperature for 5 hours.
[0145] The high-temperature single-firing process includes: heating from room temperature to 600℃ at 2℃ / min, then heating to 900℃ at 1℃ / min, and finally heating to the peak temperature at 4℃ / min and holding for 15min; after firing, cooling to 950℃ at 4℃ / min and then cooling to 750℃ at 1℃ / min.
[0146] (2) A photochromic protective glaze layer is applied to the luminous glaze substrate, and then fired at low temperature for a second time to obtain the long-lasting luminous ceramic glaze. Glazing 3 (photochromic protective glaze layer): screen printing, control the dry film thickness to 20μm, dry at 90℃ for 40min.
[0147] The low-temperature secondary firing process includes: heating from room temperature to 500℃ at 4℃ / min, then heating to 700℃ at 1℃ / min, and finally heating to the peak temperature at 7℃ / min and holding for 10 minutes; after firing, cooling to 550℃ at 1℃ / min.
[0148] The peak temperature of the high-temperature single firing is 1220℃; the peak temperature of the low-temperature double firing is 780℃.
[0149] Comparative Example 1 The difference from Example 3 is that Nb2O5 is replaced with the same mass of Al2O3.
[0150] Comparative Example 2 The difference from Example 3 is that the phosphate glass powder is replaced with the same mass of borosilicate.
[0151] Comparative Example 3 The difference from Example 3 is that zircon is replaced with the same mass of Al2O3.
[0152] Comparative Example 4 The difference from Example 3 is that WO3 is replaced with the same mass of V2O5.
[0153] Comparative Example 5 The difference from Example 3 is that CeO2 was not added.
[0154] Comparative Example 6 The difference from Example 3 is that Ba is directly applied... 1.95 Sr 0.05 SiO4:Eu 0.01 Ho 0.02 Luminous powder is used in glazing and firing.
[0155] Comparative Example 7 The difference from Example 3 is that the core-shell composite long-afterglow luminescent material is replaced with long-afterglow phosphorescent powder SrMgAl4O8:Eu.2+ Dy 3+ .
[0156] Comparative Example 8 The difference from Example 3 is that the peak temperature of the high-temperature single firing is set to 850-1000℃; The peak temperature for the low-temperature secondary firing is set to 720-750℃.
[0157] Comparative Example 9 The difference from Example 3 is that after the high-temperature first firing, the material was naturally cooled to room temperature, and after the low-temperature second firing, the material was also naturally cooled to room temperature.
[0158] The test data for Examples 1-5 are shown in Table 2.
[0159] The test data for comparative examples 1-9 are shown in Table 3.
[0160] Table 1: Raw material ratios used in Examples 1-5
[0161] Table 2: Test data for Examples 1-5
[0162] Interlayer bond strength test: Referring to GB / T31541-2015 "Test Method for Interface Bond Strength of Fine Ceramics", the specific steps are as follows: Sample preparation: Ceramic substrate (50mm×50mm×5mm) + glaze layer (thickness 0.3-0.5mm), through a complete firing process.
[0163] Use a diamond cutter to cut out small samples of 10mm×10mm×5mm to ensure the integrity of the glaze layer.
[0164] Test method: Scratch method: The critical load (Lc) at the time of glaze peeling was recorded using a nanoindenter (Anton Paar UNHT) at a rate of 50 N / min.
[0165] Tensile method: The specimen was bonded to a stainless steel fixture with epoxy resin (Araldite 2015), and a 90° peel test was performed (speed 1 mm / min). The maximum peel strength was recorded.
[0166] Medium / Strong UV transmittance test: Performed according to GB / T2680-2021 "Test Methods for Visible Light Transmittance, Solar Light Transmittance and Other Parameters of Architectural Glass": Instrument: Double-beam spectrophotometer (bandwidth ≤ 2nm, integrating sphere); Wavelength: 280nm–400nm (UVA+UVB), step size 5nm; Sample: The glaze layer is polished on one side, with a thickness of 30μm±2μm, and the substrate is a quartz sheet; Irradiation pretreatment: 500h UVA-340 aging was performed according to GB / T16422.2-2022, and then the transmittance retention rate was measured. The average values of T(365nm) and T(280-400nm) and the difference before and after aging are given.
[0167] This method is consistent with the UV transmittance testing conditions for borosilicate glass.
[0168] Outdoor charging efficiency test: using a daylight simulator (xenon lamp, spectrum matching AM1.5G, irradiance 1000W / m²). 2 The sample was irradiated under a simulator for 10 minutes, then quickly moved into a darkroom, and the initial luminance (mcd / m²) was measured using a luminance meter (Konica Minolta LS-110). 2 Record the decay curve. Charging efficiency calculation: Initial brightness divided by irradiation time (min), unit is mcd / m. 2 • min. Sample preparation: The complete glaze was coated on the ceramic substrate and tested after firing.
[0169] Afterglow time test: GB / T24982-2020 "Test Method for Luminescent Properties of Glass Surfaces" was adopted with the following supplementary measures: Excitation source: Xenon lamp + AM1.5G filter, illuminance 1000 lx, irradiation for 10 min; Detector: Luminometer (CIE127-2007 standard visual effect function correction); Environment: 25°C, RH 50%, darkroom background ≤0.01mcdm -2 ; Judgment: Record the brightness at 1 min, 10 min, and 60 min, and fit the double exponential decay to obtain τ1 and τ2; Thermal history correction: The samples were artificially aged at 200°C for 24 hours before being tested to simulate long-term outdoor heat generation.
[0170] This method has been used for the certification of long afterglow glass enamel products and is compatible with ISO 17331:2022.
[0171] Table 3: Test data for comparative examples 1-9
[0172] Note: The comparative example uses the same testing method as the embodiment.
[0173] As shown in Tables 2-3, Example 3 exhibits the best or near-best performance in all core performance indicators, including interlayer bonding strength, thermal shock resistance, response, outdoor charging efficiency, afterglow time, and weather resistance. Comparative Example 1 shows a sharp decline in interlayer bonding strength and thermal shock resistance, verifying the indispensability of Nb2O5 as a key coupling agent, forming "chemical rivets" through reaction with the underlying ions to enhance the mechanical strength of multilayer structures. Comparative Example 2 shows a decrease in interlayer bonding and thermal shock resistance, along with a slower response, demonstrating that phosphate glass has better compatibility with the upper and lower layers, forming a more stable phosphate-silicate transition layer. Comparative Example 3 shows the worst performance, especially in bonding strength and thermal shock resistance, proving that the Zr provided by zircon... 4+ It is the core element for forming a high-strength interfacial crystalline phase. Comparative Example 4 showed a strong UV transmittance of only 45%, indicating poor response, proving that WO3 is superior to V2O5 in this system as a photochromic functional material. In Comparative Example 5, the medium UV transmittance and outdoor charging efficiency were significantly lower than Example 3, but the strong UV protection capability and long lifespan were comparable to Example 3. This demonstrates that CeO2 significantly improves charging efficiency under everyday conditions. Comparative Example 6 showed significantly inferior initial brightness, afterglow time, and weather resistance compared to Example 3, demonstrating the significant advantages of the core-shell structure in improving luminescence performance and protecting phosphorescent powder. Comparative Example 7 demonstrated the multifunctionality brought about by the special structural design. Comparative Example 8 showed a comprehensive decline in all performance aspects, proving that the specific firing regime of "high temperature once + low temperature twice" is the key process to ensure the coupling of functions and interfaces of each layer. Comparative Example 9 showed the worst bonding strength and weather resistance, proving that a precisely controlled annealing regime is essential for releasing internal stress and obtaining stable products. Through systematic implementation examples, comparative designs, and data comparisons, this invention achieves interlayer chemical coupling and response optimization by introducing key components such as Nb2O5, phosphate glass, zircon, and CeO2. The core-shell luminescent powder is the core component for achieving high performance and tunable color; the two-step firing method and its precise temperature control ensure the realization of the aforementioned formulation and structural design intent.
Claims
1. A long-lasting luminescent ceramic glaze with interlayer chemical coupling, characterized in that, It is a multi-layered composite structure set on a ceramic matrix, which includes, from the inside out: The bottom layer is bonded to the glaze layer and is sintered from the first inorganic silicate raw material; The core luminescent functional glaze layer is sintered from a second inorganic silicate raw material, a long afterglow luminescent material, and niobium pentoxide, which accounts for 4-6% of the total mass of the core luminescent functional glaze layer. The photochromic protective glaze layer is composed of third inorganic glass raw materials, nano-tungsten trioxide, nano-titanium dioxide, nano-cerium oxide, and CaS:Eu. 2+ Tm 3+ It is formed by sintering.
2. The long-lasting luminescent ceramic glaze with interlayer chemical coupling according to claim 1, characterized in that, The long-afterglow luminescent material described above has a core-shell composite structure, with its core being doped with Eu. 2+ and Ho 3+ Alkaline earth metal silicates with a shell of mesoporous silica.
3. The long-lasting luminescent ceramic glaze with interlayer chemical coupling according to claim 1, characterized in that, In the aforementioned bottom bonding glaze layer, the first inorganic silicate raw material comprises, by weight percentage: feldspar 38-42%; quartz 23-27%; calcite 10-14%; zinc oxide 6-9%; kaolin 8-11%; and zircon 4-6%.
4. The long-lasting luminescent ceramic glaze with interlayer chemical coupling according to claim 1, characterized in that, The second inorganic silicate raw material is calcium-zinc borosilicate glass frit and active silica; the raw materials of the core luminescent functional glaze layer include, by weight percentage: calcium-zinc borosilicate glass frit 68-72%; long afterglow luminescent material 15-23%; active silica 4-6%; and niobium pentoxide 4-6%.
5. The long-lasting luminescent ceramic glaze with interlayer chemical coupling according to claim 1, characterized in that, The raw materials of the photochromic protective glaze layer, by weight percentage, include: 74-82% phosphate glass powder; 2-4% nano tungsten trioxide; 8-11% nano titanium dioxide; 0.5-1.5% nano cerium oxide; and CaS:Eu. 2+ Tm 3+ : 4-10%.
6. A method for preparing a long-lasting luminescent ceramic glaze with interlayer chemical coupling as described in any one of claims 1-5, characterized in that, Includes the following steps: (1) Apply a bottom layer of bonding glaze and a core luminescent functional glaze layer sequentially to a ceramic substrate, and fire it once at high temperature to obtain a luminescent glaze substrate; (2) A photochromic protective glaze layer is applied to the luminous glaze substrate, and then fired at low temperature for a second time to obtain the long-lasting luminous ceramic glaze. The peak temperature of the high-temperature single firing is 1220-1240℃; The peak temperature of the low-temperature secondary firing is 780-820℃.
7. The method for preparing long-lasting luminescent ceramic glaze with interlayer chemical coupling according to claim 6, characterized in that, The high-temperature single-firing process includes: heating from room temperature to 600°C at 2-4°C / min, then heating to 900°C at 1-2°C / min, and finally heating to the peak temperature at 4-6°C / min and holding for 15-25 minutes; after firing, cooling to 950°C at 4-6°C / min, and then cooling to 750°C at 1-2°C / min.
8. The method for preparing long-lasting luminescent ceramic glaze with interlayer chemical coupling according to claim 6, characterized in that, The aforementioned low-temperature secondary firing process includes: heating from room temperature to 500°C at 4-6°C / min, then heating to 700°C at 1-3°C / min, and finally heating to the peak temperature at 7-9°C / min and holding for 5-10 minutes; after firing, cooling to 550°C at 1-3°C / min.
9. The application of a long-lasting luminescent ceramic glaze with interlayer chemical coupling as described in any one of claims 1-5, characterized in that, Used in safety marking products for petrochemical facilities, power facilities, tunnels, offshore platforms or ships.
Citation Information
Patent Citations
Praseodymium doped red long-afterglow luminescent material and preparation method thereof
CN101177612A
Preparation method of red photon glaze
CN110066112A
Long-afterglow fluorescent glaze ceramic product and preparation method thereof
CN114133274A
Long persistence luminous sulfide material and producing method
CN1202513A
Glass / ceramic composite block luminescent material as well as preparation method and application thereof
CN120699615A
Cited By
Gold shell coated long-afterglow nano material for imaging photo-thermal and preparation and application of gold shell coated long-afterglow nano material
CN121610256A